Faktor-Faktor yang Memengaruhi Profitabilitas Bank Umum Syariah di Indonesia - Eliza Christabella Phuanerys; Yanuar Yanuar (Jurnal Manajemen Bisnis dan Kewirausahaan, 2020)
This study was conducted to analyze the effect of the Capital Adequacy, Asset Quality, Management Efficiency and Liquidity Management ratios on profitability proxied by bank Return On Assets (ROA), by analyzing the annual financial statements that have been published in 2013-2017. The variables used in analyzing the financial statements of Sharia Commercial Banks that are sampled are Asset Quality which is proxied by Non Performing Financing (NPF), Liquidity Management which is proxied by Financing to Debt Ratio (FDR), Management Efficiency proxied by Net Operating Margin (NOM), and Capital Adequacy proxied by Capital Adequacy Ratio (CAR). The sample in this study was 11 Islamic commercial banks for 5 years, namely 2013-2017. The results showed that Capital Adequacy, Asset Quality, and Liquidity Management significantly influenced the profitability of Islamic commercial banks. Whereas Management Efficiency does not affect the profitability of Islamic commercial banks. Based on these results, Sharia Commercial Banks in Indonesia must increase capital, reduce problematic financing by improving internal processes, and increase bank liquidity by increasing fundraising.